(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Study aim: to evaluate psychosocial problems of children with growth hormone deficiency. Methodology: A cross sectional study, of (80) children from both gender, (4 – 15) years diagnosed with idiopathic growth hormone deficiency, attending endocrine clinics in Baghdad city. Consent form taken from children and their guardians to participate in the study. Pediatric Psychosocial Symptoms Inventory (mood, behavioural, somatic, learning, and personality problems) was used to evaluate children psychosocial consequences. SPSS programme version 23 used for data analyses. Result: children with growth hormone deficiency experience moderate psychosocial problems, especially personality and behavioural problems. Recommendation: The researchers recommended details psychological assessment for children with growth hormone deficiency during their routine physical examination and provide suitable psychological support for them and their parent.